2021
DOI: 10.1101/2021.11.08.21266058
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Defining the determinants of under-vaccination in migrant populations in Europe to improve routine and COVID-19 vaccine uptake: a systematic review

Abstract: Diverse migrant populations in Europe are at risk of under-immunisation and have recently shown lower levels of COVID-19 vaccination intent and uptake. Understanding the determinants of vaccine uptake in migrants is critical to address immediate COVID-19 vaccination inequities, and longer-term will help improve coverage for routine vaccinations, aligning with the goals of the new Immunisation Agenda 2030. We did a systematic review following PRISMA guidelines and using a PICOS framework (PROSPERO CRD4202021921… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 97 publications
(203 reference statements)
3
19
0
Order By: Relevance
“…Tackling hesitancy and educating migrant and broader ethnic minority communities about the benefits of vaccination across the life-course will also be a critical component (22,27), with COVID-19 presenting numerous innovations in service delivery in this area that merit further consideration to routine vaccination going forward including outreach, policy shifts to facilitate registration of migrants with primary care providers, and anonymous vaccination in trusted locations (22,28). We found that certain nationality groups (Somali, Eastern-Europeans and Bangladeshi) may be more hesitant to receive vaccines than others, or reluctant to receive certain vaccines, aligning with a recent systematic review that found nationality/country of origin to be a key determinant of vaccine uptake for routine vaccines and COVID-19 vaccines in European datasets (7). In this study, acceptance barriers were mostly reported in Eastern European and Muslim migrants for HPV, measles, and influenza vaccines, with 23 significant determinants of under-vaccination in migrants found (p<0.05), including African origin, recent migration, and being a refugee/asylum seeker (7).…”
Section: Travel Vaccination and Occupational Vaccinessupporting
confidence: 84%
See 2 more Smart Citations
“…Tackling hesitancy and educating migrant and broader ethnic minority communities about the benefits of vaccination across the life-course will also be a critical component (22,27), with COVID-19 presenting numerous innovations in service delivery in this area that merit further consideration to routine vaccination going forward including outreach, policy shifts to facilitate registration of migrants with primary care providers, and anonymous vaccination in trusted locations (22,28). We found that certain nationality groups (Somali, Eastern-Europeans and Bangladeshi) may be more hesitant to receive vaccines than others, or reluctant to receive certain vaccines, aligning with a recent systematic review that found nationality/country of origin to be a key determinant of vaccine uptake for routine vaccines and COVID-19 vaccines in European datasets (7). In this study, acceptance barriers were mostly reported in Eastern European and Muslim migrants for HPV, measles, and influenza vaccines, with 23 significant determinants of under-vaccination in migrants found (p<0.05), including African origin, recent migration, and being a refugee/asylum seeker (7).…”
Section: Travel Vaccination and Occupational Vaccinessupporting
confidence: 84%
“…We found that certain nationality groups (Somali, Eastern-Europeans and Bangladeshi) may be more hesitant to receive vaccines than others, or reluctant to receive certain vaccines, aligning with a recent systematic review that found nationality/country of origin to be a key determinant of vaccine uptake for routine vaccines and COVID-19 vaccines in European datasets (7). In this study, acceptance barriers were mostly reported in Eastern European and Muslim migrants for HPV, measles, and influenza vaccines, with 23 significant determinants of under-vaccination in migrants found (p<0.05), including African origin, recent migration, and being a refugee/asylum seeker (7).…”
Section: Travel Vaccination and Occupational Vaccinessupporting
confidence: 84%
See 1 more Smart Citation
“…Higher levels of acculturation were actually found to be significant predictors of lower levels of vaccination in HPV ( 52 ) and MMR and Hepatitis B ( 53 ). On the other hand, a systematic literature review revealed that more recent (and therefore less acculturated) migrants tend to be undervaccinated ( 54 ). In the specific case of COVID-19 vaccination intention it was shown that acculturation was not a statistically significant predictor of vaccination intentions ( 55 ).…”
Section: Vaccination Behavior and Migration: Theoretical Backgroundmentioning
confidence: 99%
“…During the COVID-19 pandemic, vaccination hesitancy varies considerably among social groups that share common spaces, e.g., younger individuals, low-income communities, rural residents, or migrant populations (70,71). E.g., younger adults' concerns vary from those in other social groups as their doubts about the safety or side/adverse effects of vaccines may focus more on fertility/pregnancy (60).…”
Section: Social Spacementioning
confidence: 99%